The Evolution of The Military Personnel in The Nato Member States - Matthijs, Herman (Advances in Social Sciences Research Journal, 2023)
Based at the latest NATO annual report (NATO, 2022) this article examines the number of military personnel in the NATO (North Atlantic Treaty Organization) member states between 2014 and 2022. These two years are taken as a result of the NATO decisions at the Wales summit in 2014 to increase the defence expenditures against 2024 to 2 % of the national GDP in every member and also to invest at least 20 % of the national military budget in new material for the different army parts.